2018
DOI: 10.1007/jhep04(2018)097
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness of $$ \mathcal{N} $$ = 2 and 3 pure supergravities in 4D

Abstract: After proving the impossibility of consistent non-minimal coupling of a real Rarita-Schwinger gauge field to electromagnetism, we re-derive the necessity of introducing the graviton in order to couple a complex Rarita-Schwinger gauge field to electromagnetism, with or without a cosmological term, thereby obtaining N = 2 pure supergravity as the only possibility. These results are obtained with the BRST-BV deformation method around the flat and (A)dS backgrounds in 4 dimensions. The same method applied to n v v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…No other restrictions are made a priori, although eventually we will set limits on the number of derivatives that may appear in the gauge transformations and in the Lagrangian, therefore ensuring locality. We also assume covariance of the deformation under the (A)dS background isometry algebra, as explained in [65] to which we refer fore more details. As stated earlier, we actually consider the reformulation (and further generalization) of the deformation procedure of [64] using the BRST-BV cohomological approach spelled out in [62,63].…”
Section: Field Variablementioning
confidence: 99%
“…No other restrictions are made a priori, although eventually we will set limits on the number of derivatives that may appear in the gauge transformations and in the Lagrangian, therefore ensuring locality. We also assume covariance of the deformation under the (A)dS background isometry algebra, as explained in [65] to which we refer fore more details. As stated earlier, we actually consider the reformulation (and further generalization) of the deformation procedure of [64] using the BRST-BV cohomological approach spelled out in [62,63].…”
Section: Field Variablementioning
confidence: 99%
“…Even though, one may in general expect no new constraints but it is worth to see explicitly that the supersymmetric extension does not require any extra constraints. There has been works along this way [176], where the deformation of a free theory in the presence of both bosons and fermions were considered. It is then intriguing to consider scalar coupling from the beginning as it enhances the electric-magnetic duality symmetry group and to analyze the deformations of such a theory.…”
Section: Prospectsmentioning
confidence: 99%
“…The only other massless N = 2 supermultiplet that contains vector fields is the s = 3/2 gravitino multiplet. It has recently been shown that the s = 3/2 Rarita-Schwinger field can be coupled to vector fields consistently only as part of a graviton supermultiplet and that the N = 2 pure supergravity is unique [31]. These results show clearly that it is impossible to deform the maximal supergravity consistent with supersymmetry sourced by auxiliary vector fields along the lines of BN proposal.…”
mentioning
confidence: 95%